Age-related differences in bladder function and sexual outcomes following bipolar transurethral resection of the prostate: a retrospective cohort study - Yeni S.; DEMİR A.; Sabuncu H.; Yildiz H. E.; Ortac H. (My University, 2026)
Background: Benign prostatic obstruction negatively affects bladder emptying and, if untreated, may be associated with impaired bladder emptying and related complications. Objectives: To compare postoperative outcomes of bipolar transurethral resection of the prostate (bipolar TURP) among different age groups and evaluate the effect of patient age. Design: Retrospective cohort study. Methods: We analyzed 132 male patients who underwent bipolar TURP between May 2022 and January 2024. Patients were grouped by age: Group 1 (50–60 years), Group 2 (61–70 years), and Group 3 (⩾71 years). Pre- and postoperative parameters—including prostate-specific antigen, prostate volume, uroflowmetry (maximum and average flow rates, voided volume, post-void residual), symptom duration, medication use, and International Index of Erectile Function-5 (IIEF-5) scores—were assessed at 12 months postoperatively. Results: Group 1 demonstrated significantly greater improvements in peak flow rates, post-void residual volume, and IIEF-5 scores compared with the older cohorts (p < 0.05). While Group 3 presented with the longest symptom duration and highest medication use at baseline, multivariate regression analysis identified advancing age as an independent predictor of more limited improvement in post-void residual volume (p = 0.008) and IIEF-5 scores (p < 0.001), while its association with ∆Qmax reached only marginal significance (p = 0.050). Younger patients exhibited better postoperative preservation of erectile function and relatively improved recovery of bladder emptying. Conclusion: Patient age is associated with urinary and sexual outcomes after bipolar TURP. The strongest age-related associations were observed for postoperative recovery of bladder emptying and preservation of erectile function, whereas improvement in peak flow rate was less strongly age-dependent and should be interpreted with caution. Trial registration: Not applicable.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Üroloji ve Nefroloji; Clinical Medicine (Med); Clinical Medicine; Urology & Nephrology; Üroloji; Urology; age; benign prostatic obstruction; bipolar TURP; bladder emptying; erectile function